System of control and identification rfid applied in the unit of emergency motorized “the hawks” of the PNP - Maluquish Atalaya, Yober Ronal (2016)
Presentado Congreso Internacional Students Conference on Electrical, Electronincs and Computer Science – SCEECS 2016, Bhopal , India del 05 al 06 de marzo.